Longevity of an immunocontraceptive vaccine effect on fecundity in rats. (April 2022) - Pinkham, R.; Eckery, D.; Mauldin, R.; Gomm, M.; Hill, F.; Vial, F.; Massei, G.
Abstract: Increases in human-wildlife conflicts alongside cultural shifts against lethal control methods are driving the need for alternative wildlife management tools such as fertility control. Contraceptive formulations suitable for oral delivery would permit broader remote application in wildlife species. This study evaluated the contraceptive effect and immune response to two novel injectable immunocontraceptive formulations targeting the Gonadotropin Releasing Hormone (GnRH): MAF-IMX294 and MAF-IMX294P conjugates, both identified as having potential as oral contraceptives. The study also explored whether in multiparous species immunocontraceptives may either totally prevent reproduction or also affect litter size. Female rats, chosen as a model species, were given three doses of either MAF-IMX294 or MAF-IMX294P to compare anti-GnRH immune response and reproductive output up to 310 days post-treatment. Both formulations induced anti-GnRH antibody titres in 100% of rats and significantly impaired fertility compared to control animals. Following treatment with MAF-IMX294 and MAF-IMX294P 0 of 9 and 1 of 10 females respectively produced litters following the first mating challenge 45 days post-treatment, compared to 9 of 9 control animals. Across the whole 310 day study period 7 of 9 females from the MAF-IMX294 group and 10 of 10 females in the MAF-IMX294P group became fertile, producing at least one litter throughout six mating challenges. No significant differences were found between the two formulations in antibody titre response or duration of contraceptive effect, with an average time to first pregnancy of 166 days for MAF-IMX294 and 177 days for MAF-IMX294P for all females that became fertile. Following treatment with MAF-IMX294 and MAF-IMX294P the first litter produced post-infertility in treated females was significantly smaller than in control animals. This indicates treatment with immunocontraceptives may induce an overall suppression of fecundity extending past an initial infertility effect. This increases the potential long-term impact of these immunocontraceptives in multiparous species such as commensal rodents.